1983
DOI: 10.1128/iai.41.3.902-907.1983
|View full text |Cite
|
Sign up to set email alerts
|

Systemic candidosis in silica-treated athymic and euthymic mice

Abstract: Intravenous silica injections were used to assess the role of macrophages in the resistance of BALB/c nude and euthymic mice to systemic candidosis. CFU of Candida albicans in the kidneys, livers, and spleens of salineor silica-treated mice were enumerated at various times after inoculation with 104 viable yeast cells. The number of C. albicans organisms recovered from the kidneys of silicatreated euthymic mice was similar to the number recovered from saline-treated controls during the first 3 days of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…and other as yet unknown mechanisms may be important as well (6,40). This condition may not be significantly different from that of laboratory animals in which innate resistance mechanisms (3,9,12,23,27,30) tend to prevent the spread of the organisms until T-dependent immunity has developed sufficiently to help with clearance of the fungus (2,8,15,20,34). In agreement with this notion, we have recently shown that systemic colonization of mice with low-virulence Candida cells leads to prolonged stimulation of T cells (10) and activation of microbicidal macrophages that confer protection against an otherwise lethal C. albicans challenge (4).…”
Section: Discussionmentioning
confidence: 98%
“…and other as yet unknown mechanisms may be important as well (6,40). This condition may not be significantly different from that of laboratory animals in which innate resistance mechanisms (3,9,12,23,27,30) tend to prevent the spread of the organisms until T-dependent immunity has developed sufficiently to help with clearance of the fungus (2,8,15,20,34). In agreement with this notion, we have recently shown that systemic colonization of mice with low-virulence Candida cells leads to prolonged stimulation of T cells (10) and activation of microbicidal macrophages that confer protection against an otherwise lethal C. albicans challenge (4).…”
Section: Discussionmentioning
confidence: 98%
“…It has long been known that phagocytic cells, neutrophils (110,111) and macrophages (112,113) in particular, are crucial for recovery from initial infections with C. albicans, and that the adaptive immunity and the T cell response play only a minor role (114). This latter conclusion has been reinforced by repeated demonstrations that immunodeficient 'nude' (97,115,116) and SCID (117) mice are no more susceptible to systemic infection than euthymic controls.…”
Section: Cellular Responsesmentioning
confidence: 99%
“…A role for classical thymus-dependent cell-mediated immunity in protection against mucosal candidiasis is supported by enhanced susceptibility to this form of candidiasis in athymic mice (17,39), patients with chronic mucocutaneous candidiasis (23), and patients with acquired immunodeficiency syndrome (44). However, data on the effect of T-lymphocyte-mediated systems in protection against invasive candidiasis do not establish as clear a role (2,6,10,11,14,16,20,25,26,30,40,41). Similarly, a role for a protective effect for B-lymphocyte-mediated mechanisms is not clearly established (1,12,16,18,32,35,39).…”
mentioning
confidence: 99%